Ministry Of Higher Education (MOHE): Quality assurance on education / Norhidayah Ali...[et al.] - Ali, Norhidayah; Mohamed Isa, Zuraidah; Ibrahim, Dahlia (2010)
Quality Assurance is considered as a new area of concern among education practitioners in Malaysia. In the past, Ministry of Higher Education (MOHE) place little stress on the importance of having quality assurance among its higher education institutions. The last few years since quality assurance has become a top-notch issue in the world arena of education, MOHE started to paddle up speedily towards achieving the standard of quality recognizable globally. An accreditation such as MQA (Malaysia Qualifications Agency), formerly knows as LAN (Lembaga Akreditasi Negara) or National Accreditation Board was introduced. It is expected that the MQA accreditation will guide the Malaysian higher education system in improving the quality of education rendered to the public. Therefore, this informative paper will look at the quality assurance education: perspectives, current practice among education institutions, MOHE’s roles and public expectation of quality education.